Knowledge management system as a basis for smart learning - Natalia V. Dneprovskaya (Открытое образование (Москва), 2018)
The purpose of the study is to develop an approach to improve information support for the development of the contents of higher education programs and teaching methodological materials. The system of higher education faces the challenges of supporting the development of the digital economy through training and research. Creating the appropriate content of education becomes a difficult task with the high rate of development of digital technologies and methods to use them. Now, in smart learning, the technical aspects of the organization of the educational process often overshadow aspects, related to the methodology or content of smart learning. However, the issues of the content of education become most relevant. Research in the field of knowledge management remain relevant because, the more perfect the technologies become, that notice the algorithmized work of specialists, the higher the value of creativity for society and the economy.Materials and methods of research include discourse analysis of domestic and foreign scientific sources devoted to the issues of smart education and knowledge management, the systematization of the material. Methodological basis for developing an approach to improve information support is the methods and technologies of the theory of knowledge management.The results of the research show that the need for the development of the digital economy places high demands not only for technologies, but also primarily on the competencies for their use. The logic of IT development in education indicates that there is a gradual change in the stages of informatization: from distance education technologies to e-learning and then to smart learning. Each stage of the informatization of education allows solving the problems that are important for the economy and society. There are the factors, influencing the formation of requirements for the content of educational programs: technological, economic, social and geopolitical. The following requirements of smart training for the content of educational programs are revealed: actual information and tasks in the training course; opportunities for independent cognitive, research and project activities of students; distributed information system of smart learning; integration of the educational environment with professional communities; individualization of the content of training.The conclusion. Technologies and methods of knowledge management can provide the necessary level of speed and quality of development of educational materials. The article describes the knowledge management system, which through the knowledge base, communities and co-creation tools, ensures the relevance of the developed content and fills the smart learning with the necessary content.